A Trypsin Inhibitor from Tecoma stans Leaves Inhibits Growth and Promotes ATP Depletion and Lipid Peroxidation in Candida albicans and Candida krusei - Patriota, Leydianne L. S.; Procópio, Thamara F.; de Souza, Maria F. D.; de Oliveira, Ana Patrícia S.; Carvalho, Lidiane V. N.; Pitta, Maira G. R.; Rego, Moacyr J. B. M.; Paiva, Patrícia M. G.; Pontual, Emmanuel V.; Napoleão, Thiago H. (Frontiers in Microbiology, 2016)
Tecoma stans (yellow elder) has shown medicinal properties and antimicrobial activity. Previous reports on antifungal activity of T. stans preparations and presence of trypsin inhibitor activity from T. stans leaves stimulated the investigation reported here. In this work, we proceeded to the purification and characterization of a trypsin inhibitor (TesTI), which was investigated for anti-Candida activity. Finally, in order to determine the potential of TesTI as a new natural chemotherapeutic product, its cytotoxicity to human peripheral blood mononuclear cells (PBMCs) was evaluated. TesTI was isolated from saline extract by ammonium sulphate fractionation followed by ion exchange and gel filtration chromatographies. Antifungal activity was evaluated by determining the minimal inhibitory (MIC) and fungicide (MFC) concentrations using fungal cultures containing only yeast form or both yeast and hyphal forms. Candida cells treated with TesTI were evaluated for intracellular ATP levels and lipid peroxidation. Cytotoxicity of TesTI to PBMCs was evaluated by MTT assay. TesTI (39.8 kDa, pI 3.41, Ki 43 nM) inhibited similarly the growth of both C. albicans and C. krusei culture types at MIC of 100 µg/mL. The MFCs were 200 µg/mL for C. albicans and C. krusei. Time-response curves revealed that TesTI (at MIC) was more effective at inhibiting the replication of C. albicans cells. At MIC, TesTI promoted reduction of ATP levels and lipid peroxidation in the Candida cells, being not cytotoxic to PBMCs. In conclusion, TesTI is an antifungal agent against C. albicans and C. krusei, without toxicity to human cells.